Posttranslational Modification in Bone Homeostasis and Osteoporosis - Yuzhe Lin; Shide Jiang; Yuming Yao; Hengzhen Li; Hongfu Jin; Guang Yang; Bingzhou Ji; Yusheng Li (MedComm)
ABSTRACT Bone is responsible for providing mechanical protection, attachment sites for muscles, hematopoiesis micssroenvironment, and maintaining balance between calcium and phosphorate. As a highly active and dynamically regulated organ, the balance between formation and resorption of bone is crucial in bone development, damaged bone repair, and mineral homeostasis, while dysregulation in bone remodeling impairs bone structure and strength, leading to deficiency in bone function and skeletal disorder, such as osteoporosis. Osteoporosis refers to compromised bone mass and higher susceptibility of fracture, resulting from several risk factors deteriorating the balanced system between osteoblast‐mediated bone formation and osteoclast‐mediated bone resorption. This balanced system is strictly regulated by translational modification, such as phosphorylation, methylation, acetylation, ubiquitination, sumoylation, glycosylation, ADP‐ribosylation, S‐palmitoylation, citrullination, and so on. This review specifically describes the updating researches concerning bone formation and bone resorption mediated by posttranslational modification. We highlight dysregulated posttranslational modification in osteoblast and osteoclast differentiation. We also emphasize involvement of posttranslational modification in osteoporosis development, so as to elucidate the underlying molecular basis of osteoporosis. Then, we point out translational potential of PTMs as therapeutic targets. This review will deepen our understanding between posttranslational modification and osteoporosis, and identify novel targets for clinical treatment and identify future directions.